Required additional heating power of building during intermitted heating - Pupeikis, Darius; Burlingis, Arūnas; Stankevičius, Vytautas (Journal of Civil Engineering and Management, 2010)
By introduction of intermittent heating of building we can reduce the thermal energy consumption for heating. But it requires the additional power of heating system. It is determined that the most effective solution for energy savings is to enlarge the heating power approximately by 50% for most of buildings. The simulation has showed that for buildings with a medium thermal inertia (time constant τ = 144 h) the expenses by employing the intermittent heating (reduced temperature period: 12 h on working days and 48 h at weekends), pays back after one year. By designing the heating system we must pay attention to thermal inertia of building. Our research showed that for various thermal inertias of building, the adequate modes of intermittent heating must be chosen. Published Published Online: 24 Jun 2011